Learning Centered on The Creativity of Group B Students in The Implementation of Kurikulum Merdeka - Yeni Maryani (Jurnal Pendidikan Profesi Guru, 2023)
One of the obstacles faced by students is the low level of creativity. This is based on the minimal use of tools and materials in teacher-centred learning activities. Creativity has such an important role in a child's life. Learning that is centered on student creativity as a form of implementing the Kurikulum Merdeka learning. Learning that is centered on student creativity which is carried out during core activities with a duration of 45 minutes. This type of research is descriptive qualitative research with thematic analysis techniques, the object in this case is students aged 5-6 years, totaling 20 students and 2 class teachers. Techniques this data collection is interviews, observations, and documentation. From these data that the Kurikulum Merdeka is designed to make it easier for teachers to teach student-oriented, so that teachers are expected to be able to provide the best learning experience for all students. This stage was developed as a step or learning process to make changes to learning practices and assessments that educators need to do when using the Kurikulum Merdeka. The results of the Implementation of the Kurikulum Merdeka go hand in hand with the concept of independent learning to influence early childhood creativity so that it can develop according to their interests and learning readiness. The learning that is centered on the creativity of early childhood is in the form of a series of varied and innovative activities.